A study of prevalence of metabolic syndrome in patients with type 2 diabetes mellitus in a tertiary care referral hospital in West Bengal - Maiti, Tamoghna; Mandal, Sonai; Banerjee, Ratul; Das, Somenath; Panda, Amrita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The terms "metabolic syndrome", "insulin resistance syndrome" and "syndrome X" are now used specifically to define a constellation of abnormalities that is associated with increased risk for the development of type 2 diabetes and atherosclerotic vascular disease. It is a state of chronic low grade inflammation with the profound systemic effects. Several organisations gave several criteria to diagnose it. Effective preventive approaches include lifestyle changes, primarily weight loss, diet, and exercise, the appropriate use of pharmacological agents to reduce the specific risk factors. Methods: A cross-sectional study was done to evaluate the co-morbidity profile of patients, with metabolic syndrome and correlate clinical manifestations with specific components or metabolic syndrome, at the OPD of Bankura Sammilani Medical College and Hospitals, West Bengal. American Association of Clinical Endocrinologists criteria were chosen for diagnosis. Results: 100 patients were recruited having type II diabetes mellitus. Most of the patients were male between 20-70 years and maximum was on oral hypoglycemic agent with app 40% patient was without any glycemic control. In comorbidities hypertension was highest, followed by coronary artery disease, hypothyroidism and cerebrovascular accident. Waist-hip ratio was highest in female. All of the patients were having some cardiac risk factor assessed by ECG, echocardiography and thread mill test. Conclusions: The data demonstrates that metabolic syndrome is extremely common among diabetic patients. Frequency was much higher in women than men. Obesity is a key element in causing the metabolic syndrome and this factor was also more common in women.